2018
DOI: 10.1016/j.mod.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro method for studying subcellular rearrangements during cell polarization in Drosophila melanogaster hemocytes

Abstract: Thanks to the power of Drosophila genetics, this animal model has been a precious tool for scientists to uncover key processes associated to innate immunity. The fly immune system relies on a population of macrophage-like cells, also referred to as hemocytes, which are highly migratory and phagocytic, and can easily be followed in vivo. These cells have shown to play important roles in fly development, both at the embryonic and pupal stages. However, there is no robust assay for the study of hemocyte migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Ecdysone signalling has been shown to drive expression of phagocytic genes in pupae (28), stimulate motility and cytoplasmic rearrangements (31,62), and help establish immune responses (29). The VT62766 subpopulation exhibits enhanced wound responses, but reduced rates of phagocytosis (18), so while ecdysone could be argued to drive cells towards a more activated state, associated changes in behaviour do not completely align.…”
Section: Discussionmentioning
confidence: 99%
“…Ecdysone signalling has been shown to drive expression of phagocytic genes in pupae (28), stimulate motility and cytoplasmic rearrangements (31,62), and help establish immune responses (29). The VT62766 subpopulation exhibits enhanced wound responses, but reduced rates of phagocytosis (18), so while ecdysone could be argued to drive cells towards a more activated state, associated changes in behaviour do not completely align.…”
Section: Discussionmentioning
confidence: 99%
“…Ecdysone signalling has been shown to drive expression of phagocytic genes in pupae (Regan et al, 2013), stimulate motility and cytoplasmic rearrangements (Edwards et al, 2018; Sampson et al, 2013), and help establish immune responses (Tan et al, 2014). The VT62766 subpopulation exhibits enhanced wound responses, but reduced rates of phagocytosis (Coates et al, 2021), so while ecdysone could be argued to drive cells towards a more activated state, associated changes in behaviour do not completely align.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that Trpml-dependent Ca 2+ release from lysosomes leads to Myo-II activation and traction force generation in cultured Drosophila larval hemocytes. To gain insights into the mechanisms by which Trpml and lysosomal Ca 2+ regulate Myo-II in polarized cells, we relied on a recent method we developed that allows studying symmetry breaking in hemocytes in vitro (Edwards et al, 2018). We observed that in nonpolarized hemocytes, Myo-II as well as lysosomes were dispersed throughout the cell in wild-type and trpml 1 mutant conditions (Fig.…”
Section: Trpml Regulates Lysosome and Myo-ii Polarizationmentioning
confidence: 99%
“…We developed a method that allows pharmacological induction of hemocyte polarization for the study of organellar and cytoskeletal redistribution at high spatiotemporal resolution (Edwards et al, 2018). Briefly, glass-bottomed dishes were treated with collagen type IV (C6745; Sigma) according to manufacturer's instructions.…”
Section: Hemocyte Polarization and Subcellular Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation